(untitled) (Research, Society and Development, 2025)
Objectives: To provide an overview of Cannabis Products for medicinal purposes (CP) in Brazil, focusing on technical and regulatory aspects and problems that have been detected in the national market from 2020 to 2024. Methodology: This study employed a descriptive approach, involving searches on the official website of the Brazilian regulatory agency (Anvisa) to gather information on regular and irregular CP. Results and Discussion: A total of 19 companies, located in the central-west, southeast, and south regions of Brazil, were authorized to manufacture or import CP. Of these companies, six engage in national production using imported inputs, while the others import final products from countries such as Canada, the United States, Switzerland, Colombia, and Uruguay. A total of 56 products were collected, which consisted of oral solutions of standardized or isolated cannabidiol (CBD) in various concentrations (17.18 to 200 mg/mL). The analysis of 29 sanitation inspection reports revealed irregularities in companies and products, primarily related to online commerce. The suspension and banning of advertising were frequent precautionary measures. Conclusion: In recent years, Brazil has made progress in regulating CP, facilitating access to CBD solutions. The role of Health Surveillance is relevant to ensure CP with quality and patient safety. As the development and standardization of Cannabis-based products continue to advance, several sectors can expect future challenges.